Novel hybrid method to additively manufacture denser graphite structures using Binder Jetting - Popov, Vladimir V.; Fleisher, Alexander; Muller-Kamskii, Gary; Shishkin, Andrei; Katz-Demyanetz, Alexander; Travitzky, Nahum; Goel, Saurav (Nature Publishing Group, 2021)
This study introduces two hybrid processes integrating an additive manufacturing technique with post-processing treatments namely (i) Binder Jetting Printing (BJP) + Cold Isostatic Pressing (CIP) + cycle and (ii) BJP + cycle where cycle refers to a sequence of Impregnation—Drying—Pyrolysis. These two new processes yielded additively manufactured parts with higher density and reduced defects/porosities. As a testbed, we used these new processes to fabricate graphite structures. The samples produced by both methods were compared with each other and benchmarked to the samples produced by (a) BJP alone and (b) Traditional uniaxial pressing like compaction moulding. Various characterisation methods were used to investigate the microstructure and mechanical properties which showed that the porosity of hybrid manufactured samples reduces from 55% to a record 7%. This technological pathway is expected to create a new avalanche of industrial applications that are hitherto unexplored in the arena of hybrid additive manufacturing with BJP method.
Keywords: Hybrid Manufacturing; Graphite structures; Binder Jetting Printing; Binder impregnation; pyrolysis; porosity; high-density